Upaya Meningkatkan Aktivitas Belajar Siswa dan Hasil Belajar Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning dan Metode Permainan Engklak di Kelas X Kc.2 SMK Negeri 10 Medan - Sugiman Sugiman (Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to describe the increase in learning activities and learning outcomes and student learning outcomes through the use of the problem based learning model and the engklak game method in class X Kc.2 SMK Negeri 10 Medan. This type of research is Classroom Action Research. The subjects of this research were 32 female students in class X Kc.2 of SMK Negeri 10 Medan. The procedure or method used in this research consists of two cycles with stages, namely: (1) planning, (2) implementation (action), (3) observation, (4) reflection. Students' Mathematics learning activities using the Problem based learning method and the engklak game experienced an increase, in cycle I where the indicator of enthusiasm for the subject matter was (96.87%) and increased in cycle II, namely (97.91%), the indicator of identifying problems increased from ( 42.71%) in cycle I increased to (68.75%) in cycle II, indicators of cooperation in groups increased from (61.72%) to (65.67%) in cycle II, and indicators of concept understanding (39, 1%) increased in cycle II to (84.34%).